2011
DOI: 10.1002/anie.201103802
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Cytotoxic and Actin‐Depolymerizing Biotin Derivatives of Aplyronine A

Abstract: Tied up: a PEG-linked biotin derivative of marine macrolide aplyronine A (ApA) is shown to exhibit potent cytotoxicity and cause actin disassembly in tumor cells. This method of introducing a PEG linker at the end of the aliphatic tail should offer perspectives for developing and using versatile actin-targeting molecular probes. PEG=poly(ethylene glycol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…Recent work has shown that aplyronine A causes caspase-dependent apoptosis with rapid disassembly of the actin cytoskeleton and dephosphorylation of focal adhesion kinase 10 and has suggested an interaction between the aplyronine–actin complex and a secondary biomolecule such as Arp2/3. 11 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that aplyronine A causes caspase-dependent apoptosis with rapid disassembly of the actin cytoskeleton and dephosphorylation of focal adhesion kinase 10 and has suggested an interaction between the aplyronine–actin complex and a secondary biomolecule such as Arp2/3. 11 …”
mentioning
confidence: 99%
“…1116 Moreover, they hold great potential for the development of biomolecular probes and novel actin-targeting therapeutic agents. It is a testament to the severe challenge presented by these complex polyketides that, despite considerable effort from several groups, 1216 only one prior total synthesis of aplyronines A–C has been achieved, as reported by Yamada and Kigoshi.…”
mentioning
confidence: 99%
“…Based on the MS/MS analysis of tryptic peptide fragments and immunoblotting analysis, we confirmed that these proteins were actin-related proteins 2/3 (Arp2 and Arp3), respectively. 46 Both Arp2 and Arp3 were also competitively eluted by 5 from the resin as with actin (lane 2). These results suggested the presence of specific interactions between ApA and actin-related proteins.…”
Section: Award Accountsmentioning
confidence: 97%
“…45 Here we describe the development and use of the ApA derivatives, that is, investigations of their target proteins and dynamic behavior in tumor cells. 46,47 3.1 Synthesis and Biological Activities of ApA Derivatives. Previous studies of the structureactivity relationship 48 and photoaffinity labeling experiments 49 have established that the C24C34 aliphatic tail part of 5 is important for potent actin-depolymerizing activity.…”
Section: 43mentioning
confidence: 99%
See 1 more Smart Citation